Artikel tentang penelitian di tahun 2018 - Khrisne, Duman Care (International Student Conference on Electrical and Computer Engineering (ISCECE); Proceedings of 2018 International Student Conference on Electrical and Computer Engineering (ISCECE), 2021)
Artikel tentang penelitian di tahun 2018